Implementation of a routine respiratory follow-up after prematurity less than 32 weeks gestation or below 1,500 g birthweight at preschool age—a two-year experience - Höck, Michaela; Zschocke, Anna; Pupp-Peglow, Ulrike; Marcher, Carolin; Brunner, Barbara; Schütz, Maria; Kiechl-Kohlendorfer, Ursula; Griesmaier, Elke (Frontiers in Pediatrics, 2025)
BackgroundGrowing evidence indicates that prematurity adversely affects lung function, even in early childhood, thus, a routine respiratory follow-up was implemented in our clinical setting. The aim of this study was to evaluate the acceptance of this examination and assess the feasibility of forced expiratory maneuvers and bronchodilator responsiveness test (BRT) in former preterm infants at preschool age and to present initial results.MethodsIn November 2022, a respiratory follow-up was implemented for former preterm infants born at less than 32 weeks of gestation or with a birth weight below 1,500 g, who were born between 2016 and 2019 at Innsbruck Medical University Hospital. The evaluation included a standardized clinical examination, collection of medical history, spirometry, and a BRT.ResultsA total of 107 former preterm infants (median gestational age 29.9 (28.1; 31.1) weeks and mean birthweight 1,250.5 (±355.6) grams performed spirometry. Successful spirometry was achieved by 93 (86.9%) children. Among these, 64 (59.8%) had normal pulmonary function and were symptom-free, however, ten (15.6%) showed a positive BRT. Twenty-nine children (27.1%) exhibited pathological test results and/or respiratory symptoms, with 13 (44.8%) of them testing positive for bronchial hyper-responsiveness. Fourteen children (13.1%) did not meet the quality control criteria for spirometry but were symptom-free.ConclusionOur study demonstrated that a respiratory follow-up for preterm infants is highly accepted and feasible at preschool age. Up to 30% of infants were identified with impaired lung function and subsequently received appropriate management, highlighting the importance of standardized and routine respiratory follow-up for these children.